MONOLINGUAL DICTIONARY VS BILINGUAL DICTIONARY EFFECTIVENESS AND DICTIONARIES FEATURES TOWARD STUDENTS' WRITING TEXS IN ISLAMIC SENIOR HIGH SCHOOL INTERNATIONAL STANDARD OF AMANATUL UMMAH - M.ROMDON ASY'ARI (2014)
The dictionary could be one of the best tools to help learners to acquire the second language (L2). There are two kinds of dictionary compared in this study; they are monolingual dictionary and bilingual dictionary. In this case the writer compares both kinds of dictionaries in order to know the impact of using them in writing course conducted at the senior high school level. This study may help the learners choose the most appropriate dictionary in their learning process.